PANCASILA SEBAGAI SISTEM FILSAFAT DALAM KONSEP HUKUM DI INDONESIA - Zaskia Hanyfah; Agnes Oktapia, Mirtha Tirta P, Dhea Amalia Fatikha, Zainudin Hasan (INTELIGENSIA MEDIA, 2024)
Article 1 Paragraph 3 of the 1945 Constitution confirms that Indonesia is a country that adheres to a legal system or in other words Indonesia is a country of law. Therefore, in its application the concept of the rule of law in Indonesia must be in harmony with the values that live and develop in society. Pancasila is an embodiment and strengthening of the noble norms of the Indonesian people whose existence is very important in implementing the concept of the rule of law in Indonesia. Therefore, the application of legal concepts in Indonesia requires Pancasila as its philosophical basis. The method in this research uses a normative juridical method, namely by examining positive law from various aspects, one of which is the theoretical, historical and philosophical aspects that bind the legal system used. The aim of this research is to understand the concept of law in Indonesia based on the Pancasila philosophical system. The results of this research show that The results of this research show that Pancasila can be called a state philosophical system because in essence all legal formation as well as its application and implementation cannot be separated from the values of Pancasila as Staatsfundamentalnorm. Furthermore, the legal concept in Indonesia which is based on the Pancasila philosophical system has the characteristics of being pluralistic in society, diverse in culture, polite and courteous in religion, as well as order in maintaining other social values.